2013
DOI: 10.1155/2013/839270
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Excision of Cardiac Myxoma and Endovascular Coiling of Intracranial Aneurysm after Cerebral Infarction

Abstract: Cardiac myxoma is the most common primary tumor of the heart, located mainly in the left atrium. Cerebral embolization or intracranial aneurysm formation as a consequence of left atrial myxomas has been well documented, whereas myxoma embolization causing the combination of cerebral infarction and intracranial myxomatous aneurysm is rare. We report herein, a 67-year-old female with a cardiac myxoma who experienced a left hemispheric embolic ischemic stroke and in addition was found to have right internal carot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 15 publications
1
21
1
Order By: Relevance
“…Nineteen (14.3%) patients had other than cerebral artery embolisms, with systemic multiple emboli in 4 (21.1%) [ 55 , 63 , 71 , 80 ] , peripheral multiple emboli in 3 (15.8%) [ 19 , 72 , 85 ] and solitary arterial embolus in 12 (63.2%) patients [ 9 , 11 , 13 , 16 , 21 , 35 , 41 , 43 , 60 , 76 , 84 ] . The 39 affected arteries in 18 patients were listed in Table 8 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nineteen (14.3%) patients had other than cerebral artery embolisms, with systemic multiple emboli in 4 (21.1%) [ 55 , 63 , 71 , 80 ] , peripheral multiple emboli in 3 (15.8%) [ 19 , 72 , 85 ] and solitary arterial embolus in 12 (63.2%) patients [ 9 , 11 , 13 , 16 , 21 , 35 , 41 , 43 , 60 , 76 , 84 ] . The 39 affected arteries in 18 patients were listed in Table 8 .…”
Section: Resultsmentioning
confidence: 99%
“…Al-Said et al. [ 11 ] disagreed the use of recombinant tissue plasminogen activator for intravenous thrombolysis due to probable myxoma source infarct. Vogel et al [ 80 ] suggested a 4-week delay of surgical resection of cardiac myxoma concerning the risk of intracerebral hemorrhage following cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, 1 patient presented with recurrent cerebral infarction caused by a partially thrombosed 1.7 cm myxomatous oncotic aneurysm. Previous studies have examined endovascular embolization, chemotherapy, and radiation in the treatment of such aneurysms, and the findings are equivocal (15)(16)(17)(18)(19)(20). Therefore, the optimal treatment of myxomatous oncotic aneurysms needs to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal treatment of myxomatous oncotic aneurysms has not been established. Prior studies examining the role of endovascular embolization, chemotherapy, and radiation in decreasing the growth of these aneurysms have yielded equivocal results [5,24,25] .…”
Section: Intracranial Aneurysms In Myxoma Patientsmentioning
confidence: 99%